THE EFFECT OF USING OUTLINES ON IDEA DEVELOPMENT QUALITY OF STUDENTS ESSAY WRITINGS - Salija, Kisman (International Journal of Language Education, 2017)
The study dealt with the entity and process of essay writings both using and without using an outline. It aimed at finding out (1) the idea development quality of two essays by using outline, (2) the idea development quality of two essays without using outline, and (3) the significant difference of idea development quality of the two essays with and without using outlining strategy. The study was experimental with factorial and repeated measure design. The results showed that using outlining strategy was significantly better than without using it, and the comparison indicated the same results as classification both with and without outlines. It was strongly recommended that the pre-writing strategy was extremely pivotal to have good idea quality development.Â